ANALYSIS OF DIVIDEND POLICY (STUDY OF MANUFACTURING COMPANIES REGISTERED ON INDONESIA STOCK EXCHANGE) - Dahlia Pinem; Rahmat Kuncoro Aji (Journal of Management and Leadership, 2020)
This study aims”to examine the effect of Liquidity (CR),Leverage (DER), Profitability (ROE) on Dividend Policy. The object of this study is a manufacturing company registered on the stock exchange in 2016- 2018. From 147companies that became the population, there were 107 selected samples obtained by using random sampling through the Slovin formula. Data regression analysis performed is a data panel consisting of cross-sections of data and time series processed by using Microsoft Excel and E-views. The test conducted in this study show that (1) liquidity with the current ratio has no significant effect on the dividend policy, (2) leverage with the proxy of debt to equity ratio has a significant effect on the dividend policy, (3) profitability with the proxy of return on equity ratio has no significant effect and has a negative relationship with dividend policy.